Development of Mathematics Learning Media Based on Augmented Reality and Unity 3D - Fauzi, Moch.; Ridho'i, Mohammad (Aksioma Education Journal, 2024)
This study aims to explore the effectiveness of the use of augmented Reality-based learning media (AR) in improving students ' understanding of abstract mathematical concepts. By utilizing AR and Unity3D Technology, students are provided with a more interactive and visual learning experience through 3D objects that enable a clearer understanding of concepts. The results showed that AR-based learning media is effective in helping students understand difficult math materials, increasing their motivation, and involvement in learning. In addition, positive perceptions from teachers and students regarding the use of AR were also revealed, where this medium is considered to be able to facilitate teaching and make students more interested and active in learning. However, the study also found some challenges, such as limited devices that can support AR applications optimally and difficulties in integrating AR with existing curricula. This research suggests further development in technology and infrastructure to improve the effectiveness of the use of AR-based learning media in the future.